ANALISIS KAPASITAS SUNGAI CIPARIGI TERHADAP DEBIT BANJIR KALA ULANG - Saputra, Lingga; Hariati, Feril; Alimuddin, Alimuddin (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2018)
Ciparigi is a natural canal that flow across the North of Bogor District. The length of reach around 8.700 m and the freeboard is depth. In previous years, a catchment area of Ciparigi was safe from flood. But recently, around 2015, flooding event was occurred in this area. To find out the root of problem, hydrological analysis and hydraulics analysis were applied. From hydrologic analysis, maximum flood discharge for return periode 2, 5, and 25 year respectively were 59,057 m3/dtk, 66,817 m3/dtk, dan 80,716 m3/dtk. While the average capacity of canal was about 40 m3/s. From the comparison value between existing capacity of canal and maximum flood discharge for each return period, we found out that the flooding event mostly triggered by the reduction of width and depth of canal in downstream area, and caused backwater effect and flooded the upstream area